O transporte escolar como política pública de acesso e permanência dos alunos na escola Santa Bárbara, no município de Acará/PA: um estudo sobre qualidade e condições de execução - ALVES, Valdeci Cristo (2025)
This article analyzes the school transportation policy from the perspective of ensuring access and retention of rural students in a riverside school, through field research using a qualitative approach, as well as through the analysis of documents relevant to the topic. In addition to the regulations and some theoretical foundations, we explore the practical experience of students from the Santa Bárbara school who use school transportation, where we verify some conditions under which the policy is implemented, from the perspective of the technical specifications provided for in the legislation. Our results reveal that the school transportation policy is fundamental to guarantee the right to education of rural students, but that improvements are necessary and possible. This study contributes to the discussion on the implementation of technical and management measures aimed at improving the school transportation service.